2023
DOI: 10.1073/pnas.2207003120
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H 2 receptor deficit in glutamatergic neurons contributes to the pathogenesis of schizophrenia

Abstract: Schizophrenia is a serious mental disorder, and existing antipsychotic drugs show limited efficacy and cause unwanted side effects. The development of glutamatergic drugs for schizophrenia is currently challenging. Most functions of histamine in the brain are mediated by the histamine H 1 receptor; however, the role of the H 2  receptor (H 2 R) is not quite clear, especially in schizophrenia. Here, we found that expression of H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Interestingly, one OXTRDEG -Plgrkt -is involved in lactation 46 , a well-known function of OXTR signaling. Other OXTRDEGs, Hrh2, Kynu and Recq1, have been associated with social disability [47][48][49] , supporting the notion that OXTR signaling influences social phenotypes in both health and disease.…”
Section: Genetic Deletion Of Oxtr Reveals That Oxtr Signaling Mediate...mentioning
confidence: 88%
“…Interestingly, one OXTRDEG -Plgrkt -is involved in lactation 46 , a well-known function of OXTR signaling. Other OXTRDEGs, Hrh2, Kynu and Recq1, have been associated with social disability [47][48][49] , supporting the notion that OXTR signaling influences social phenotypes in both health and disease.…”
Section: Genetic Deletion Of Oxtr Reveals That Oxtr Signaling Mediate...mentioning
confidence: 88%
“…Histamine is a neurotransmitter that plays a significant role in immune response, inflammation, wakefulness, appetite control, and cognition, and it is involved in various CNS disorders, including schizophrenia [33,83]. The central histamine activity was detected to be heightened in patients with chronic schizophrenia, and the lack of the histamine receptor gene resulted in the manifestation of negative symptoms of schizophrenia [84][85][86].…”
Section: Neurotransmitters and Their Role In Schizophreniamentioning
confidence: 99%
“…The neuromodulator histamine is synthesized by neurons located in the tuberomammillary nucleus (TMN) of the hypothalamus which send wide-spread axonal projections and release histamine throughout the central nervous system (Haas & Panula, 2003;Haas et al, 2008;Lin et al, 2023). Although classically assumed to mainly regulate the sleep-wake cycle, the histaminergic system is now thought to have many more diverse physiological roles in a multitude of brain regions and stages of life (Schwartz et al, 1991;Takahashi et al, 2006;Panula et al, 2014;Han et al, 2020;Lucaci et al, 2023), and has been shown to be dysfunctional in various neurological and neurodevelopmental disorders (Ercan-Sencicek, 2010; Shan et al, 2015;Carthy & Ellender, 2021;Xu et al, 2022;Ma et al, 2023). For example, Tourette's syndrome (TS) is an earlyonset disorder that is characterized by involuntary motor and vocal tics often comorbid with obsessive-compulsive disorder (OCD) and depression (Robertson et al, 2017) and parallel findings in patients and mouse models suggest that a disruption of the histaminergic system and reduced levels of histamine can be part of the etiology (Ercan-Sencicek, 2010;Fernandez et al, 2012;Karagiannidis et al, 2013;Baldan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%